2022
DOI: 10.5614/j.eng.technol.sci.2022.54.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Al on ZnO Electron Transport Layer in Perovskite Solar Cells

Abstract: Perovskite solar cells have shown remarkable performance and improvements in terms of solar cell efficiency. The ETL material is one of the important components in perovskite solar cells in conducting electrons to produce current. Here, ZnO was used as ETL material in a perovskite solar cell using the SCAPS 1D simulation software. The ZnO ETL showed poor cell efficiency due to its reaction with the perovskite material. A small amount of Al doped into ZnO was introduced to enhance the physiochemical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Table 1. Parameters used for simulation of perovskite solar cell structures using SCAPS-1D [19,[23][24][25][26] Parameters FTO ZnO:Al CsSnGeI3 C u I Thickness (μm) Band gap energy E g (eV) Electron affinity χ (eV) Relative permittivity ϵ r Effective conduction band density N c (cm −3 ) Effective valance band density N v (cm −3 ) Electron thermal velocity (cm/s) Hole thermal velocity (cm/s) Electron mobility μ n (cm 2 V −1 s −1 ) Hole mobility μ p (cm 2 V −1 s −1 ) Donor concentration N D (cm −3 ) Acceptor concentration N A (cm −3 ) Defect density N t (cm −3 ) 0.4 3.5 4.3 9 2.2×10 18 1.8×10 19 1.0×10…”
Section: Theoretical Methods and Device Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Table 1. Parameters used for simulation of perovskite solar cell structures using SCAPS-1D [19,[23][24][25][26] Parameters FTO ZnO:Al CsSnGeI3 C u I Thickness (μm) Band gap energy E g (eV) Electron affinity χ (eV) Relative permittivity ϵ r Effective conduction band density N c (cm −3 ) Effective valance band density N v (cm −3 ) Electron thermal velocity (cm/s) Hole thermal velocity (cm/s) Electron mobility μ n (cm 2 V −1 s −1 ) Hole mobility μ p (cm 2 V −1 s −1 ) Donor concentration N D (cm −3 ) Acceptor concentration N A (cm −3 ) Defect density N t (cm −3 ) 0.4 3.5 4.3 9 2.2×10 18 1.8×10 19 1.0×10…”
Section: Theoretical Methods and Device Structurementioning
confidence: 99%
“…The most commonly used ETLs are metal oxides such as TiO 2 , ZnO and SnO 2 , their electrical properties can be tailored by doping [22]. The impact of Aluminium (Al) on zinc oxide (ZnO) as ETL in PSCs was studied by Alias et al [23]. In their study, only the properties of the ETL and interface were explored and a PCE, up to 17.59% was obtained for 1 mol% Al concentration in ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…Both aluminium (Al) and zinc (Zn) are abundant, cost-effective, and non-toxic elements with ample availability. Doping with Al offers multiple benefits, including enhancing the stability of the ZnO/perovskite interface 114 by modifying the fundamental properties of ZnO, 115 but also significantly improves the carrier concentration and electron mobility of the material performance, as discussed in Section 5 regarding diffusion theory. 116 In 2014, Mahmood et al revealed that the PCE of PSC with AZO films deposited via electro spraying rises from 10.8% to 12.0%.…”
Section: Influences Of Dopants On Zno As Etl In Pscmentioning
confidence: 99%
“…This work represents a significant step towards optimizing electron transport layers for more efficient solar cell devices. 20 Rai et al conducted a study on the optimization of the hole transporting layer (HTL) for improving the performance of Pb-free double PSCs. Utilizing numerical simulations, the researchers aimed to identify the most effective HTL material and its thickness.…”
Section: Introductionmentioning
confidence: 99%